A Highly Selective NIR Fluorescent Turn-on Probe for Hydroxyl Radical and Its Application in Living Cell Images - Qu, Xingyu; Song, Wenting; Shen, Zhen (Frontiers in Chemistry, 2019)
A highly selective NIR fluorescent turn-on probe for hydroxyl radical (·OH) has been built up using triphenylphosphine as a reactive-site for ·OH in an energy transfer cassette 2b consisting of 8-2’-(thiophen-2-yl) quinoline (TQ) as a donor and 3,5-diphenylphosphinostyryl-substituted BODIPY as an acceptor, which exhibits ca. 317 nm pseudo Stokes’ shift due to efficient through-bond energy transfer (up to 169 %). The triphenylphosphine substituent of 2b selectively oxidized by ·OH over the other reactive oxygen species (ROS) and the reactive nitrogen species (RNS) resulting in fluorescence enhancement in aqueous solution and in living cells.